Analisis Biaya Produksi Mesin Ball Mill Skala Laboratorium - Alfie, Fahmi Putra; Fitri Ganda, Andita Nataria; Sakti, Arya Mahendra (Universitas Negeri Surabaya, 2025)
The ball mill is one of the essential machines used to reduce material size to the micro and nano scale. At the laboratory level, this machine is highly beneficial for research and technology development, yet its production cost often becomes a challenge. This study aims to analyze the production cost of a laboratory-scale ball mill in detail as a reference for more efficient planning. The research method applied an experimental approach by directly manufacturing one unit of the ball mill, starting from design planning, material procurement, fabrication process, up to cost calculation. All data covering material requirements, labor costs, and process expenses were calculated based on manufacturing standards. The results showed that the total production cost of the laboratory-scale ball mill was IDR 3,807,491, consisting of material costs of IDR 3,094,600, process costs of IDR 512,891, and planning costs of IDR 200,000. With a profit margin of 35%, the recommended selling price was IDR 5,140,112 per unit. This study emphasizes the importance of production cost analysis as a basis for budget control, price determination, and machine development strategies at both laboratory and small-scale industrial levels.